Desires for active ageing technology. Issue 138 (June 2020) - De Angeli, Antonella; Jovanović, Mlađan; McNeill, Andrew; Coventry, Lynne
Highlights: Active ageing technologies have a generalised tendency to ground their design on a model of ageing that portrays people in decline. We propose a structured methodology to collect user requirements as desires. We define a model of user desires in terms of the person (described through attitudes, perceived norms and personal agency) and the sociotechnical context of use. The model is used to define new design trajectories for active ageing technology as design for pleasurable and resourceful ageing. Abstract: Several technological devices have been developed over the last decade to support an active lifestyle as people age. Despite substantial investment, they have failed to reach widespread acceptance. Limited adoption can be linked to little involvement of prospective users in the design process and overreliance on deficit models of ageing that portray people in decline. The paper proposes a structured methodology to collect user requirements based on the Integrated Behavioural Model. The methodology was applied in an interview study investigating behavioural intentions of preferred activities in a sample of 18 older users. Results have been elaborated as desires for actions in a model which puts the person (described in terms of attitudes, perceived norms and personal agency) to the forefront of the designer's attention. The model is contrasted with related work on technology adoption and used to define trajectories for active ageing technology as design for pleasurable and resourceful ageing.